Small fibers, large impact: Quality of life in small‐fiber neuropathy. Issue 3 (28th June 2013) - Bakkers, Mayienne; Faber, Catharina G.; Hoeijmakers, Janneke G.J.; Lauria, Giuseppe; Merkies, Ingemar S.J.
ABSTRACT Introduction: The impact of small‐fiber neuropathy (SFN) on patients' quality of life (QOL) has not been studied extensively. Our aim was to determine the impact of SFN on QOL and examine possible determinants. Methods: We examined a total of 265 patients diagnosed with SFN. The SFN Symptoms Inventory Questionnaire (SFN‐SIQ), the pain Visual Analog Scale (VAS), and the generic SF‐36 Health Survey were assessed. Regression studies were undertaken to evaluate determinants of functioning. Results: SFN patients demonstrated a severe overall reduction in QOL. The biggest deficits were in Role Functioning–Physical, Body Pain, and Physical Component Summary (PCS) scores. VAS scores, changed sweating pattern, dry mouth, and age were the strongest predictors for PCS, explaining 32% of the QOL decrease. Conclusions: SFN leads to a reduction in overall QOL. The presence of pain and some autonomic symptoms explained only a small portion of the findings. Muscle Nerve49:329–336, 2014